Fault-tolerant control of clutch actuator motor in the upshift of 6-speed dry dual clutch transmission. (February 2020) - Zhao, Zhiguo; Jiang, Siwen; Ni, Runyu; Fu, Shihao; Han, Zhiyu; Yu, Zhuoping
Abstract: As the working hours of dual clutch transmission (DCT) increase, the probability of a fault occurring in the clutch actuator motor increases. If no fault-tolerant control is adopted after an actuator motor fault occurs, it will lead to shifting failure and even damage the actuator motor. This study devises corresponding fault-tolerant control strategies for 6-speed DCT vehicle when the actuator motor of one of the clutches malfunctions in the upshift process. In those strategies, once the actuator motor fails, the vehicle is designed to disengage the fault clutch and engage the no-fault clutch, after which the vehicle can be driven either in the current gear or in higher/lower gear by jumping upshift with single clutch depending upon the driver demand. This ensures that the vehicle maintains better power performance and fuel economy even after a fault occurs in one clutch actuator motor. Lastly, the strategies were verified in the DCT hardware-in-the-loop test bench. Highlights: A DCT dynamic model in upshift process and the clutch actuator model were built. A fault classification by the fault motor performance was proposed. Fault-tolerant control strategies for clutch actuator motor fault was proposed. Proposed fault-tolerant control strategies were verified on HIL test bench.